Optimising psychological treatment for Anxiety DisordErs in Pregnancy (ADEPT): study protocol for a feasibility trial of time-intensive CBT versus weekly CBT - Fiona L. Challacombe; Laura Potts; Ben Carter; Vanessa Lawrence; Alaina Husbands; Louise M. Howard (Pilot and Feasibility Studies, 2021)
Abstract Background Moderate to severe anxiety disorders such as obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), social phobia and panic disorder are common, and affect approximately 11–16% of women in pregnancy. Psychological treatments for anxiety disorders, primarily cognitive behaviour therapy (CBT), have a substantial evidence base and recently time-intensive versions have been found as effective as weekly treatments. However, this has not been trialled in women who are pregnant, where a shorter intervention may be desirable. Methods The ADEPT study is a feasibility randomised controlled trial with two parallel intervention groups. Time-intensive one-to-one CBT and standard weekly one-to-one CBT delivered during pregnancy will be compared. Feasibility outcomes including participation and follow-up rates will be assessed, alongside the acceptability of the interventions using qualitative methods. Discussion The study will provide preliminary data to inform the design of a full-scale randomised controlled trial of a time-intensive intervention for anxiety during pregnancy. This will include information on the acceptability of time-intensive interventions for pregnant women with anxiety disorders. Trial registration https://doi.org/10.1186/ISRCTN81203286 prospectively registered 27/6/2019.